E-015 Perioperative anticoagulation after flow diversion of large and fusiform vertebrobasilar aneurysms. (22nd July 2018) - Tsai, J; Hardman, J; Moore, N; Hussain, M; Masaryk, T; Bain, M; Toth, G
Abstract : Introduction: Increasing data suggest flow diversion with the Pipeline embolization device (PED; Medtronic) may be a safe and effective treatment in select cases of basilar artery (BA) and vertebrobasilar (VBA) aneurysms. However, coverage of vertebrobasilar perforators and branches by the PED carries an estimated 8%–13% risk of perioperative stroke, especially in cases of large and/or fusiform aneurysms. Systemic anticoagulation may moderate thrombosis rate in the immediate postoperative period, but is not routinely used due to the potential risk of hemorrhagic complications with concomitant dual antiplatelet therapy. We reviewed the safety of perioperative heparinization in patients with PED embolization of BA and VBA aneurysms. Materials and methods: Using procedure codes in the clinical database, we identified patients with posterior circulation aneurysms treated with flow diversion and received heparin infusion. Based on radiological reports, we selected patients with BA and VBA large and fusiform aneurysms. We extracted data from their electronic medical records, including baseline patient characteristics, perioperative antithrombotic regimens and laboratory data, device number and specifications, and clinical outcomes. We reviewed all available neuroimaging to ascertain aneurysm characteristics and radiological outcomes. Results: Between 2009 and 2018, we identified a total of 7 patients (mean age 51 years [IQR 46–63]) with BA or VBA aneurysms, who underwent 8 Pipeline embolization and also received perioperative heparinization in the neurological ICU. All reached a target activated PTT (aPTT) level 1.5–2 times of the upper normal limit. Median duration of anticoagulation was 2 (IQR 1–2.3) days. All patients were also therapeutic on concomitant dual antiplatelet therapy. The median number of PEDs placed per patient was 2 (IQR 2–3). Three (37.5%) cases had adjunctive coil embolization. No intracranial or major systemic hemorrhage occurred. Complications while on anticoagulation included 1 (12.5%) self-limiting oropharyngeal mucosal hemorrhage, 1 (12.5%) sudden cardiac arrest, and 1 (12.5%) cerebellar stroke without long-term sequelae. Conclusion: In our single-center experience, perioperative heparinization in a monitored ICU setting showed no association with intracranial or major systemic hemorrhage. More data are needed to optimize its role in the perioperative management of BA and VBA aneurysms treated with flow diversion. Disclosures: J. Tsai: None. J. Hardman: None. N. Moore: None. M. Hussain: None. T. Masaryk: None. M. Bain: 2; C; Stryker. G. Toth: None.